Analisis Algoritma Insertion Sort, Merge Sort Dan Implementasinya Dalam Bahasa Pemrograman C++ - Arief Hendra Saptadi; Desi Windi Sari (JURNAL INFOTEL, 2012)
This paper presents the study of implementation and performance in sorting process, using two different algorithms, namely Insertion Sort and Merge Sort. In the first stage, the two algorithms were implemented in C++ language to sort several numbers typed by a user. In the second stage, the source codes for those algorithms were modified to enable sorting randomly generated numbers with the amount as requested by the user. To find out how well they performed in sorting out the data, therefore in the last stage the two algorithms were tested to sort random numbers with predetermined amount ranges and the results were compared. From the experiments performed, merge sort algorithm had shown a better performance, particularly in a large number of data (> 10000). Insertion sort algorithm has the advantage in lower complexity algorithm, notably in the best case condition and since it does not use recursion routines in sorting process, hence it does not require as much storage space or memory as needed by merge sort algorithm.